The Lymphatic Anatomy of the Lower Eyelid and Conjunctiva and Correlation with Postoperative Chemosis and Edema. Issue 3 (March 2017) - Shoukath, Sajna; Taylor, G. Ian; Mendelson, Bryan C.; Corlett, Russell J.; Shayan, Ramin; Tourani, Saam S.; Ashton, Mark W.
Abstract : Background: There are minimal data in the literature regarding the lymphatic drainage of the conjunctiva and lower eyelid and the relationship with postoperative chemosis and edema. Methods: Injection, microdissection, and histologic and radiologic studies were conducted on 12 hemifacial fresh cadaver specimens. Indocyanine green lymphography was conducted in five volunteers. Results: Histology identified lymphatic vessels superficial and deep to the orbicularis oculi. Cadaveric dissection, injection, and radiographic studies identified interconnecting superficial and deep facial lymphatic systems and a conjunctival lymphatic network draining through the tarsal plate to the deep lymphatic system. The superficial lymphatic collectors traveled in subcutaneous fat within the lateral orbital and nasolabial fat compartments. The lateral deep lymphatic collectors traveled beneath orbicularis oculi, then through the superficial orbicularis retaining ligament, and into the sub–orbicularis oculi fat in the roof of the prezygomatic space. These vessels descended to preperiosteal fat at the level of zygomaticocutaneous ligaments to travel adjacent to the facial nerve into preauricular nodes. Indocyanine green lymphography identified correlating draining pathways laterally to the parotid nodes and medially to submandibular nodes. Conclusions: The authors have found that the lower eyelid and conjunctiva are drained by interconnecting superficial and deep lymphatic systems of the face. The superficial system is vulnerable to damage in incisions and dissection in the infraorbital area. The deep system is vulnerable to damage in dissection around the orbicularis retaining ligament and the zygomaticocutaneous ligaments. The authors suggest that concurrent damage to both the superficial and deep lymphatic systems, especially laterally, may be responsible for postoperative chemosis and edema.